Glycemia Carrion's disease and the dog Bartonellosis - Pons Muzzo, Julio (1942)
The author studied the glycemia, prior to food being taken, in normal subjects, in patients suffering from Oroya Fever, and in dogs infected with Bartonella canis. 1. A moderate hyperglycemia, can be proved to exist, with certain frequency, in the hematic stage of Carríon's disease. 2. These changes in the glycemia, are also present, in the experimental dog Bartonelosis, during the stage of intense anemia. 3. An occasionally severe hypoglycemia, probably causing the animals death, often accompanies the terminal stage of serious cases of dog Bartonelosis, and follows the hyperglycemia whenever these two phenomena occur in one and the same case. 4. The hyperglycemia proved to exist both in subjects suffering Irom Carrion's disease, and in dogs seized with Bartonelosis can be explained as being due to an exagerated hepatic glycogenolysis, stimulated by the infectious state and also possibly by the anaemic anoxia. 5. The exhaustion of the glycogene reserve of the liver, caused mainly by an over-consumption of glucose, and by the reduced capacity of the liver to fix this substance, and the probable inhibition of the neoglycogenolysis, would be the factors causing the hypoglycemic condition occurring in serious cases of dog Bartonelosis.